2020
DOI: 10.3390/surfaces3020019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and CO Oxidation Performance of Ag2O/γ-Al2O3 and (Ag2O+RuO2)/γ-Al2O3 Catalysts

Abstract: This research dealt with the preparation and characterization of silver oxide (SLO) nanomaterials (NMs) and their composite catalysts (i.e., silver and ruthenium oxide (SLORUO)). The prepared materials were tested for their catalytic performance in carbon monoxide (CO) oxidation. Generally, silver in its pure state is not widely used for CO oxidation due to stability and structural issues. However, the usage of subsurface oxygen and oxygen-induced reconstruction could be effective as an oxidation catalyst at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…Authors suggested that the CO molecule directly reacts with a surface O atom neighboring the Pd dopant, leading to the formation of CO 2 and a surface O vacancy, without any activation energy. Ananth et al [43] studied the CO oxidation on RuO 2 /Al 2 O 3 catalyst, and showed complete CO oxidation at 200˚C, 225˚C, and 300˚C, similar to these results obtained for the same temperature range and at space velocity between 2000 and 2657 (mL/min.g). Therefore, it can be attributed to the high distribution and dispersion of metal oxide over an MWCNT, due to the high surface area, which influences the CO 2 selectivity.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Authors suggested that the CO molecule directly reacts with a surface O atom neighboring the Pd dopant, leading to the formation of CO 2 and a surface O vacancy, without any activation energy. Ananth et al [43] studied the CO oxidation on RuO 2 /Al 2 O 3 catalyst, and showed complete CO oxidation at 200˚C, 225˚C, and 300˚C, similar to these results obtained for the same temperature range and at space velocity between 2000 and 2657 (mL/min.g). Therefore, it can be attributed to the high distribution and dispersion of metal oxide over an MWCNT, due to the high surface area, which influences the CO 2 selectivity.…”
Section: Discussionsupporting
confidence: 60%
“…Results showed graphitic carbon at 284.3 eV [41]. Peaks at 284.5 and 290.5 eV are assigned to the carbon atoms (C-C) attached to groups containing oxygen (C=O) in their structure [43]. The electronic transition of orbitals π → π* was associated with the peak at 290.5 eV.…”
Section: X-ray Spectroscopy (Xps) Of Ru/mwcntmentioning
confidence: 96%
“…For Ag-Al2O3 nanosheets, Ag 3d3/2 and Ag 3d5/2 XPS peaks were observed at BEs of 374.5 eV and 368.6 eV, respectively. This was attributed to metallic Ag [6,32,36]. The shoulder [15,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum oxide (Al 2 O 3 ) has extensively been used as a heterogeneous catalyst in diverse catalytic reactions of CO oxidation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], CO 2 reduction [20][21][22][23], CO 2 methanation/hydrogenation [20,[24][25][26][27], and preferential oxidation of CO [28,29]. The efforts to increase the catalytic activity of the metal oxide have been devoted to the modification of the metal surface by loading of transition metals in groups of 9 (Co, Rh, and Ir), 10 (Ni, Pd, and Cu), and 11 (Cu, Ag, and Au).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation